# |
ODE |
Mathematica |
Maple |
\[
{}x^{\prime \prime } = 50
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime } = -20
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime } = 3 t
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime } = 2 t +1
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime } = 4 \left (3+t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime } = \frac {1}{\sqrt {t +4}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime } = \frac {1}{\left (t +1\right )^{3}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime } = 50 \sin \left (5 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-10 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-15 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+5 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+3 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }-y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+8 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}6 y^{\prime \prime }-7 y^{\prime }-20 y = 0
\] |
✓ |
✓ |
|
\[
{}35 y^{\prime \prime }-y^{\prime }-12 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime }-y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-5 y^{\prime \prime }+8 y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+9 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 3 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 12
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-3 y = 6
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+2 y = 2 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y = 6 x +4
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-5 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }-3 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-10 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }-7 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+5 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+8 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}5 y^{\prime \prime \prime \prime }+3 y^{\prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-8 y^{\prime \prime \prime }+16 y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-3 y^{\prime \prime \prime }+3 y^{\prime \prime }-y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime \prime }+12 y^{\prime \prime }+4 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+3 y^{\prime \prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-8 y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+18 y^{\prime \prime }+81 y = 0
\] |
✓ |
✓ |
|
\[
{}6 y^{\prime \prime \prime \prime }+11 y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime } = 16 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }-y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+3 y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }+6 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime \prime }-3 y^{\prime \prime }-2 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime \prime }+2 y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+10 y^{\prime \prime }+25 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime \prime }-y^{\prime \prime }-5 y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+27 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y^{\prime \prime \prime }+y^{\prime \prime }-3 y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }+4 y^{\prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }-3 y^{\prime \prime }-5 y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }-54 y = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime \prime }-2 y^{\prime \prime }+12 y^{\prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}6 y^{\prime \prime \prime \prime }+5 y^{\prime \prime \prime }+25 y^{\prime \prime }+20 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime \prime }+11 y^{\prime \prime }+4 y^{\prime }-14 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime } = y^{\prime \prime \prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-5 y^{\prime \prime }+100 y^{\prime }-500 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 i y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-i y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \left (-2+2 i \sqrt {3}\right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime } = y^{\prime \prime \prime }+y^{\prime \prime }+y^{\prime }+2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = {\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }+2 y = 3 x +4
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-6 y = 2 \sin \left (3 x \right )
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }+y = 3 x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+4 y^{\prime }+7 y = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = \sinh \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = \cosh \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-3 y = 1+x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+9 y = 2 \cos \left (3 x \right )+3 \sin \left (3 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+4 y^{\prime } = 3 x -1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime } = 2-\sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = {\mathrm e}^{x} \sin \left (x \right )
\] |
✓ |
✓ |
|